2021
DOI: 10.3390/cancers13194851
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Post-Operative Radiotherapy in Early Stage (pT1-pT2N0M0) Oral Tongue Squamous Cell Carcinoma in Era of DOI

Abstract: Background: This study investigated the role of depth of infiltration (DOI) as an independent prognosticator in early stage (T1-T2N0M0) oral cavity tumors and to evaluate the need of postoperative radiotherapy in the case of patients upstaged to pT3 for DOI > 10 mm in the absence of other risk factors. Methods: We performed a retrospective analysis on patients treated with surgery and re-staged according to the 8th edition of malignant tumors classification (TNM). The role of DOI as well as other clinical/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Rajappa et al 29 demonstrated that the addition of PORT on the basis of DOI did not show significant survival benefits in pT1-2N0M0 OTSCC. Similar results were also obtained by Alterio et al 14 and Rubin et al 30 Conversely, Liao et al 25 margin ≥5 mm is commonly considered adequate in OTSCC, 20 yet alternative proposals by Zanoni et al 20 and Tasche et al 23 suggest cutoffs of 2.2 mm and 1 mm for improved risk stratification in oral cancer, respectively. Conversely, some authors found no association between margin status and local recurrence in T1-2N0 oral cancer.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Rajappa et al 29 demonstrated that the addition of PORT on the basis of DOI did not show significant survival benefits in pT1-2N0M0 OTSCC. Similar results were also obtained by Alterio et al 14 and Rubin et al 30 Conversely, Liao et al 25 margin ≥5 mm is commonly considered adequate in OTSCC, 20 yet alternative proposals by Zanoni et al 20 and Tasche et al 23 suggest cutoffs of 2.2 mm and 1 mm for improved risk stratification in oral cancer, respectively. Conversely, some authors found no association between margin status and local recurrence in T1-2N0 oral cancer.…”
Section: Discussionsupporting
confidence: 71%
“…6,7 In deed, the clinical benefit of PORT in patients with early-stage OTSCC is highly controversial, 12,13 with uncertain risk factors. [14][15][16][17][18][19] In the absence of a definitive randomized clinical trial, a large retrospective study may be helpful. This study, which included the largest cohort (528 cases) of patients with pT1-2N0M0 OTSCC, aimed to evaluate the role of PORT in early-stage OTSCC and identify subgroups that may benefit from PORT.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the uniformity of indications for postoperative therapies did not seem to be influenced by the T migration of the TNM system, since the final pathological staging is impacted by the status of N in the case of ECE+ 20 .…”
Section: Discussionmentioning
confidence: 96%
“…These factors are known prognostic factors in oral cancer ( 66 , 67 ), but, to date, their role has not yet been evaluated in terms of the difference between men and women.…”
Section: Discussionmentioning
confidence: 99%